THE FORMATION OF METHEMOGLOBIN BY STREPTOCOCCUS VIRIDANS - Blake, Francis G. (The Rockefeller University Press, 1916)
Cultures of Streptococcus viridans when brought into contact with red blood corpuscles have the power of transforming oxyhemoglobin into methemoglobin. The reaction occurs only in the presence of living streptococci when they are able to carry on their metabolic activities. The intensity of the reaction runs roughly parallel with the period of growth and multiplication of the bacteria and gradually diminishes and disappears as growth ceases. There is no apparent relation between the activity of a given strain of Streptococcus viridans in producing methemoglobin and its source or virulence. If the streptococci are suspended in salt solution they are unable to change oxyhemoglobin into methemoglobin unless some nutrient substance is present. Of the various nutrient substances tested dextrose is the most efficient in enabling the organisms to bring about the reaction. The reaction does not occur in the absence of oxygen, and is retarded by an excess of oxygen. Substances which tend to reduce the metabolic activities of the bacteria to a minimum exert an inhibitory action on methemoglobin formation. While not definitely proving it to be so, the results obtained in the above experiments strongly support the supposition that the reaction is not due to injurious substances produced by the bacteria or to products arising from the decomposition of the nutrient material present, but rather to the metabolic activities of the bacteria themselves when they are surrounded by environmental conditions which render growth and multiplication possible. The exact chemical nature of the change of oxyhemoglobin to methemoglobin is not known, but it is probably an oxidation process or a combination of reduction and oxidation processes, as pointed out by Heubner. As Cole has shown, the action of aminophenol is of great interest in this connection, in that it acts like a catalytic agent in being able to transform much more hemoglobin into methemoglobin than would be possible if the reaction were a simple molecular one. The metabolic activities of bacteria are largely in the nature of oxidation and reduction processes. The transformation of oxyhemoglobin into methemoglobin by streptococci of the viridans type, therefore, may be analogous to the action of such substances as aminophenol, and the reaction may be due to the active oxidation and reduction processes occurring in the neighborhood of the bacterial cells. The failure of the reaction to occur in the absence of oxygen and its retardation in the presence of an excess of oxygen, both with streptococci and with pneumococci (Cole) would seem to support this theory. Such results, however, may be due to the abnormal conditions surrounding the bacteria with consequent inhibition of their metabolic activities. Cole concluded as the result of his study of methemoglobin formation by pneumococci that since bacteria may injure red blood cells apparently by disturbances in oxidation in the immediate neighborhood of the organisms rather than by the production of a definite toxin, it is possible that bacteria may injure other tissue cells in a like manner and that the pathological effects produced by these bacteria may be explained on this basis. The experimental results recorded above have shown that the formation of methemoglobin by Streptococcus viridans in no way differs from its formation by pneumococci, and they lend support to the theory that bacteria may be injurious to tissues because of the disturbances in oxidation brought about by the metabolic activities of the organisms, especially those associated with growth and multiplication. It is believed that this theory may be particularly applicable to the pathological effects caused by Streptococcus vindans because the lesions produced by it, whether single or multiple, both in man and in experimental animals, are prone to be localized and associated with the actual presence of the streptococci in the lesions.